EVALUATING THE IMPACT OF INTERPROFESSIONAL COLLABORATION AND CONTINUOUS EDUCATION ON MEDICATION SAFETY AND ORAL HEALTH OUTCOMES IN SAUDI ARABIAN HEALTHCARE SETTINGS - Abdul Kareem Aiesh Alharbi, Aishah Eissa Alanazi, Hathlol Hassan Alrashed, Motleg Hassan Alrashed, Salman Huimed Almutairi, Yasser Shaman Almutairi, (Chelonian Research Foundation, 2022)
Interprofessional collaboration and continuous education are essential for improving healthcare quality and patient safety. This study aims to evaluate the impact of these factors on medication safety and oral health outcomes in Saudi Arabian healthcare settings. A mixed-methods approach was employed, combining a cross-sectional survey of healthcare professionals and a retrospective analysis of patient records. The study included 600 healthcare professionals (300 pharmacy technicians and 300 dental hygienists) and 1,200 patient records from six hospitals and six dental clinics across Saudi Arabia. The data were analyzed using descriptive statistics, multiple regression, and content analysis. The results showed that interprofessional collaboration and continuous education were significant predictors of medication safety and oral health outcomes. The qualitative findings revealed that effective communication, shared decision-making, and ongoing training were key facilitators of interprofessional collaboration and continuous education. The study highlights the importance of fostering a culture of collaboration and lifelong learning in healthcare organizations and provides recommendations for policy and practice in Saudi Arabia. Keywords: interprofessional collaboration, continuous education, medication safety, oral health outcomes, pharmacy technicians, dental hygienists, Saudi Arabia